2021
DOI: 10.3390/polym13172866
|View full text |Cite
|
Sign up to set email alerts
|

DPD Study on the Interfacial Properties of PEO/PEO-PPO-PEO/PPO Ternary Blends: Effects of Pluronic Structure and Concentration

Abstract: Using the method of dissipative particle dynamics (DPD) simulations, we investigated the interfacial properties of PEO/PEO-PPO-PEO/PPO ternary blends composed of the Pluronics L64(EO13PO30EO13), F68(EO76PO29EO76), F88(EO104PO39EO104), or F127(EO106PO70EO106) triblock copolymers. Our simulations show that: (i) The interfacial tensions (γ) of the ternary blends obey the relationship γF68 < γL64 < γF88 < γF127, which indicates that triblock copolymer F68 is most effective in reducing the interfacial tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Our model is constructed based on both our previous work and relevant studies in the field. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] The obtained outcomes hold significant implications for comprehending the PLA-b-PEO-b-PLA drugloaded system, thereby providing valuable insights for the design and formulation of optimized polymeric micelles with enhanced drugloading capabilities.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Our model is constructed based on both our previous work and relevant studies in the field. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] The obtained outcomes hold significant implications for comprehending the PLA-b-PEO-b-PLA drugloaded system, thereby providing valuable insights for the design and formulation of optimized polymeric micelles with enhanced drugloading capabilities.…”
mentioning
confidence: 90%
“…In this study, we investigate the influence of the PLA block length, the PLA‐ b ‐PEO‐ b ‐PLA copolymer concentration, and the paclitaxel drug content on the morphologies and structures of paclitaxel‐loaded PLA‐ b ‐PEO‐ b ‐PLA micelles using dissipative particle dynamics (DPD) simulations. Our model is constructed based on both our previous work and relevant studies in the field 24–42 . The obtained outcomes hold significant implications for comprehending the PLA‐ b ‐PEO‐ b ‐PLA drug‐loaded system, thereby providing valuable insights for the design and formulation of optimized polymeric micelles with enhanced drug‐loading capabilities.…”
Section: Introductionmentioning
confidence: 97%
“…Other polymers with mucopenetration ability are poloxamers, also known as Pluronic ® . These block copolymers consist of hydrophilic poly (ethylene oxide) (PEO), and hydrophobic block-poly (propylene oxide) (PPO) ordered in an A-B-A triblock structure: PEO-PPO-PEO [ 172 , 173 , 174 ]. Díaz et al demonstrated that the addition of mucoadhesive and thermosensitive poloxamer 407(F127)-based hydrogels to CS microspheres in a formulation for nasal and conjunctival ram immunization improved both local and systemic humoral immune responses against the BLSOmp31 antigen, an outer membrane protein of Brucella spp., along with the reduced excretion of Brucella ovis [ 175 ].…”
Section: Enhancement Of Epithelial Permeability By Polymer-based Adju...mentioning
confidence: 99%
“…where υ S is the volume fraction of the polymer in the swollen gel; l is the length of the C-C bond along the polymer backbone (0.154 nm); C n is the Flory characteristic ratio of the polymer; M c is the average molar mass between cross-links; M r is the molecular mass of the repeated unit, V d is the volume ratio of water at equilibrium. The characteristic ratio C n was taken as the weighted average of C n values for poly(AA), SA, and PEO chains, according to their molar ratio in the hydrogel: poly(AA) = 6.7 [33], SA = 21.1 [34] and PEO = 4.98 [35].…”
Section: Measurements Of Gel Fraction Swelling and Network Parametersmentioning
confidence: 99%